2018
DOI: 10.1002/adma.201801743
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Next‐Generation Perovskite Nanocrystal Scintillator for Nondestructive X‐Ray Imaging

Abstract: Readily commercializable and cost-effective next-generation CsPbBr perovskite nanocrystals (PNCs) based X-ray detectors are demonstrated. The PNCs-based X-ray detector exhibits higher spatial resolution (9.8 lp mm at modulation transfer function (MTF) = 0.2 and 12.5-8.9 lp mm for a linear line chart), faster response time (≈200 ns), and comparable stability (>40 Gy s of X-ray exposure) compared with the commercialized terbium-doped gadolinium oxysulfide (GOS)-based detectors (spatial resolution = 6.2 lp mm at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
242
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(255 citation statements)
references
References 29 publications
2
242
1
Order By: Relevance
“…We have shown the progress in the research of scintillators from the seventy-year-old earliest traditional scintillators, NaI:Tl + and CsI:Tl + [56], the first lanthanide-doped scintillators discovered in the late eighties, Ce 3+ , Pr 3+ , and Nd 3+ doped LaF 3 [93] and YAG [118], to the very recent perovskite scintillators [22,170,171]. Lanthanide-doped scintillators already offer excellent scintillation properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown the progress in the research of scintillators from the seventy-year-old earliest traditional scintillators, NaI:Tl + and CsI:Tl + [56], the first lanthanide-doped scintillators discovered in the late eighties, Ce 3+ , Pr 3+ , and Nd 3+ doped LaF 3 [93] and YAG [118], to the very recent perovskite scintillators [22,170,171]. Lanthanide-doped scintillators already offer excellent scintillation properties.…”
Section: Resultsmentioning
confidence: 99%
“…The perovskite scintillator prototype is then used to image the internal circuitry of an iPhone as shown in Figure 7m. Separately, Heo et al demonstrated that, compared to a commercial GOS : Tb detector, CsPbBr 3 nanocrystal scintillator exhibits higher ratio of light output power/absorptivity, faster response time, and higher spatial resolution [171]. All those results [170,171] are very promising for (nanocrystal) perovskite scintillators, showing that they have the potential to replace current scintillators as a low-cost, high yield alternative.…”
Section: Perovskite Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al reported an Au/SnO 2 /CsPbBr 3 (11 µm)/spiro‐OMeTAD/ITO structure visible light detector which exhibited a responsivity of 0.172 A W −1 and a detectivity of 4.8 × 10 12 Jones and the on/off ratio up to 1.3 × 10 5 under illumination of 473 nm (100 mW). Chen et al and Heo et al take the CsPbBr 3 as a scintillator detector in X‐ray detection, respectively. However, there must be a loss of energy due to the mechanism of indirect X‐ray detector, thus reducing the sensitivity of the detector.…”
Section: Comparison Of the Relevant Device Parameters Of The X‐ray Dementioning
confidence: 99%
“…Since the revolutionary discovery of novel nanocrystal scintillators by Liu and co-workers, advances of CsPbBr 3 PNCs based scintillators have been made in the last year. Im and co-workers [9] developed a CsPbBr 3 PNCs based X-ray detector with high-performance scintillating abilities. Zhang et al [10] reported the scintillating properties of easily accessible CsPbBr 3 nanosheets colloidal and solid film scintillators.…”
mentioning
confidence: 99%